1992
DOI: 10.1190/1.1443196
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of four least‐squares inversion schemes for studying equivalence in one‐dimensional resistivity interpretation

Abstract: The problem of equivalence in dc resistivity inversion is well known. The ability to invert resistivity data successfully depends on the uniqueness of the model as well as the robustness of the inversion algorithm. To study the problems of model uniqueness and resolution, theoretical data are inverted using variations of a nonlinear least‐squares inversion. It is only through model studies such as this one, where the true solutions are known, that realistic and meaningful comparisons of inversion methods can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…In such cases, it is recommended that, as a general guide, the inverted model for the first or second iteration be taken as the optimum model. The results are in agreement with deductions by Simms and Morgan (1991) that in the 1D inversion of resistivity sounding data, the minimum data rms error and the minimum model rms error do not always coincide and that choosing the best model based on the minimum data rms error will not always give the optimum model. Although there could be other suitable statistical measures for comparing the goodness‐of‐fit between the inverted model parameters and the known theoretical model, the model rms error was found to be simple and straightforward.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In such cases, it is recommended that, as a general guide, the inverted model for the first or second iteration be taken as the optimum model. The results are in agreement with deductions by Simms and Morgan (1991) that in the 1D inversion of resistivity sounding data, the minimum data rms error and the minimum model rms error do not always coincide and that choosing the best model based on the minimum data rms error will not always give the optimum model. Although there could be other suitable statistical measures for comparing the goodness‐of‐fit between the inverted model parameters and the known theoretical model, the model rms error was found to be simple and straightforward.…”
Section: Discussionsupporting
confidence: 90%
“…This is best carried out with synthetic data since in such cases the true solutions are known. This type of study has been conducted for the 1D inversion of sounding data by Simms and Morgan (1991). However, as far as the authors are aware, no such systematic investigation has been reported for 2D inversion, and for this reason the present work has been carried out.…”
Section: Introductionmentioning
confidence: 99%
“…The applicability of SIS was extended to magnetotellurics sounding data by Gupta et al (1996) and Sri Niwas et al (2007). The efficiency and robustness of SIS are tested extensively and compared with existing popular methods taking a benchmark continuous model (Parker, 1984;Sims and Morgan, 1992),…”
Section: Modified Sis -Brief Descriptionmentioning
confidence: 99%
“…Measurement errors further increase the ambiguity of field data. This problem is well investigated in a 1D interpretation of geoelectrical sounding data (Koefoed, 1979;Militzer and Weber, 1985;Telford et al, 1990;Simms and Morgan, 1992). The calculation of ''equivalent models'', i.e., different parameter sets that fit the data equally well within the acceptable error boundaries, is usually implemented with 1D interpretation software (e. g. Resix Plus, v2, Interpex).…”
Section: Introductionmentioning
confidence: 99%